How virtual team leaders cope with creativity challenges. Issue 3 (3rd April 2017) - Han, Soo Jeoung; Chae, Chungil; Macko, Patricia; Park, Woongbae; Beyerlein, Michael
Abstract : Purpose: As technology-mediated communication improves, many organizations increasingly use new types of collaborative online tools to promote team-based learning and performance. The purpose of this study is to explore how virtual team leaders cope with process challenges in developing a context for team creativity. Design/methodology/approach: The authors interviewed nine leaders who have worked for more than five years and managed virtual teams in different fields. Findings: This research uncovered distrust, personality differences, generational differences in views, scheduling issues and technology difficulties as the top five inhibitors for virtual team creativity and success. The authors identified seven main strategies for developing virtual team creativity and success. The authors found that building "team norms" and guidelines to encourage positive interactions between team members can facilitate team creativity. In addition, a concept of trust-based open communication was identified as one of the important strategies when teams actively use technology-mediated communication tools. Practical implications: Organizational practitioners can use the results of this study when developing knowledge to establish assessments regarding which employees possess the appropriate characteristics to lead virtual teams and implement virtual team training. Originality/value: This study emphasizes the importance of technology in professional lives by showing how technology-mediated work leads to success in learning and producing creative ideas and performance in a virtual team environment.